The Trend Of Corruption The Medan District Court - Kusbianto, Kusbianto; Tarmizi, Tarmizi; Sulistyowati, Sri (Universitas Dharmawangsa, 2026)
This study aims to analyze trends in corruption cases and the characteristics of defendants based on the level of education in the Corruption Court at the Medan District Court Class 1A specifically in the period 2020-2024. The method used is a quantitative descriptive approach by utilizing secondary data in the form of case decisions obtained from The Case Tracking Information System (SIPP). The results showed that the trend of corruption cases has increased significantly over the past five years, with a total of 596 cases and 611 defendants. From a demographic aspect, the majority of defendants are men, while women are relatively fewer. Based on the level of education, most of the defendants have a higher education background, especially Bachelor (S1), followed by master (S2) and doctorate (S3). These findings indicate that corruption is not directly influenced by the level of education, but rather related to internal factors such as greed and abuse of power. Therefore, efforts to eradicate corruption not only require a repressive approach through law enforcement, but also a preventive approach through anti-corruption education and strengthening moral integrity.